Trends in financing of basic education in Ghana – a political economy analysis - Adamba, C. (International Journal of Educational Management, 2023)
Purpose – Using a political economy framework, this paper examines the financing trend, by investigating three systematic spikes occurring between 2004 and 2016. The study aims to provide a useful review of the interaction of politics, financial decisions and educational outcomes. Additionally it provides a useful guide, especially to academics, to identify political and economic conceptualizations that will predict expenditure decision-making of political actors and to be able to provide policy advice on the future effect of such decisions on availability and accessibility of public goods. Design/methodology/approach – The paper adopts a secondary data analysis approach, drawing upon secondary data sources such as from the Ministry of Education, budget statements from the Ministry of Finance, as well as relevant policy documents. Additional information for the study was also extracted from the manifestos of the two leading political parties in Ghana – the New Patriotic Party and the National Democratic Congress and their viewpoints on financing of education in Ghana. Findings – Using two epochal years when financing of education peaked (2008 and 2012), which coincided with election years, the trend lends itself to being interpreted as opportunistic spending. It appears to give credence to a conclusion that the increases in spending are more politically directed and nonneutral. Originality/value – This paper fulfills an identified need to study the trend of basic education financing in Ghana, which will help policy actors make better-informed decisions with the introduction of the novel “adaptive opportunism” framework analysis tool.
Research Article
Keywords: Social justice; Adaptive opportunism, Financing basic education; Free compulsory universal basic education; Free senior high school policy